A retrospective study of dogs with Babesia gibsoni infection presented to University Veterinary Hospital, Universiti Putra Malaysia January 2010 - December 2017 - Muhammad Imran Mohd Ramdzan. (2019)
Canine babesiosis is an important protozoal disease in dogs commonly characterized by haemolytic anemia. There are two main Babesia species known to infect dogs in Malaysia, B. vogeli and B. gibsoni. However, there is lack of data published on Babesia gibsoni infection in canine patients despite its prevalence, particularly in our local setting. Hence, this study aimed to document the signalment and histology of patients diagnosed with B.gibsoni infections, laboratory abnormalities, treatment protocols utilized and the outcome, and potential prognostic factors. Thirty dogs with B.gibsoni infections were selected and retrospectively evaluated. Basic information was collected for descriptive statistics of the survivor patient data on their history, concurrent medical conditions, and post-treatment prognosis. Findings of patient included a history of tick infestation (56.7%, n=17), outdoor management (76.7%, n=23) and exposure to other dogs (43.3%, n=13). Anemia (90.0%, n=27) and thrombocytopaenia (83.3%, n=25) were the most common haematological abnormalities. However, a number of patients also showed jaundice (23.3%, n=7) and vomiting (30%, n=9). As for concurrent medical conditions, the most prevalent disease that occurred along with babesiosis was chrlichiosis (30%, n=9). Treatment with diminazene aceturate and blood transfusion, along with increased packed cell volume (PCV) are predictors for good survivability, which supports findings from other studies.